The Effect of the Explicit Instruction Learning Model on the Poetry Writing Skills of Seventh-Grade Students: Evidence from a Junior High School in Bengkulu, Indonesia - Era Pitriana; Heny Friantary; Feny Martina (JPI: Jurnal Pustaka Indonesia, 2023)
This study examines the effect of the Explicit Instruction learning model on the poetry writing skills of seventh-grade students at SMPN 19 Bengkulu, Indonesia. Employing a quasi-experimental design with a nonequivalent control group, the study involved 30 students divided into experimental and control classes. Data were collected through pre-tests and post-tests to measure learning outcomes, supported by instrument validation and reliability testing (r₁₁ = 0.902). The results indicate that students in the experimental group achieved significantly higher post-test scores (M = 82.92) compared to the control group (M = 71.88). Independent sample t-test results confirmed a significant difference (t = 5.043, p < 0.05), suggesting that the Explicit Instruction model fosters more substantial improvement in poetry writing than conventional teaching methods. These findings underscore the pedagogical value of structured, teacher-guided approaches in enhancing literary expression among junior high school learners. Implications for curriculum design and teacher practice are discussed, alongside recommendations for future research.